SAT0503 A Prospective Single-Centre Study on Indicators of Infectious Risk After Rituximab Therapy in Children and Adolescents with Rheumatic Diseases. (9th June 2015) - Speth, F.; Hinze, C.; Haas, J.-P.
Abstract : Background: Rituximab (RTX) is used in refractory paediatric rheumatic diseases (PRD). Data regarding the effects of RTX on the immune system in children and safety in PRD is scarce. Objectives: To prospectively evaluate indicators of humoral immunity before and until 2 yrs after RTX administration. Methods: 20 patients (pts) with PRD (4 SLE, 3 MCTD, 3 JIA, 2 eosinophilic fasciitis, 2 juvenile dermatomyositis, 2 Sjögren-syndrome, 2 GPA (Wegener), 1 MPA, 1 PM/Scl-overlap) after exclusion of common variable immunodeficiency (CVID) received at least 1 standard dose RTX cycle (some pts up to 3 cycles). Additional treatment consisted of prednisolone (10), hydroxychloroquin (10), mycophenolate mofetil (9), methotrexate (6), leflunomide (4), abatacept (2), everolimus (2), cyclosporin (1) and antiinflammatory doses of intravenous immunoglobulin (IVIG) (3). Lymphocyte subpopulations, IgA, IgG, IgM and IgE levels, IgG subclasses, isoagglutinin titers, IgG levels to tetanus toxin, H. influenzae type B (Hib), pneumococcus and measles, spleen size, presence of Howell-Jolly bodies and throat culture were obtained 6, 12 and 24 months (mos) after RTX. IgG levels and vaccine titers in pts receiving IVIG were not included. The continuous variables at time points 6, 12 and 24 mos were compared by paired T test to time point 0 mo (prior to RTX). Results: All pts achieved complete B cell depletion. B cells repopulated in all pts with a median of 8.5 mos. IgG and IgM levels were as follows (median [interquartile] mg/dl at 0, 6, 12, 24 mos): IgG 1302 [898;1993], 1172 [839;1409], 902 [732;1248], 1165 [805;1580]; IgM 100 [73;174], 55 [39;85], 33 [28;59], 44 [35;51]. Significant reductions were observed for IgG (6/12 mos), IgM (6/12/24 mos), IgA (6/12/24 mos) and IgE (24 mos). Overall, 7/17 (41%) of patients received IVIG substitution based on predefined threshold levels (3/4 after 3rd cycle of RTX). 1 pt developed low IgG2/3, IgA and IgM levels at 24 mos after one cycle of RTX. 2 pts developed low IgG4 levels. Tetanus toxin IgG decreased significantly at 12 mos but not below a protective threshold. There was a non-significant decrease in pneumococcal antibodies at 12 and 24 mos. Measles IgG levels decreased significantly at 12 and 24 mos but not below a protective threshold. Isoagglutinin titers were present in all pts throughout 24 mos ruling out CVID. There was a remittent non-significant decrease in spleen size. However transient Howell-Jolly bodies indicating temporary hyposplenism were observed in 8 pts. Throat culture following RTX demonstrated colonization with C. albicans in 12, S. aureus in 3, Hib in 2, both P. aeruginosa and S. marcescens in 1, E. coli in 1 and Enterobacter in 1 pts. There were no pneumonias requiring hospitalization. Conclusions: Transient IgG-/IgM-deficiency occasionally occurs after RTX treatment of PRDs, especially after repeated treatment cycles, whereas protracted humoral immunodeficiency is very rare. Preventive strategies, including IVIG substitution and/or antibiotic prophylaxis informed by immunologic studies are effective in preventing serious invasive infections. Therefore, we suggest at least 2 yrs of surveillance for acquired humoral immunodeficiency and one-time immunization titers after RTX treatment in PRD. Acknowledgements: Supported by a grant from "Verein Hilfe für das rheumakranke Kind". Disclosure of Interest: None declared